2022
DOI: 10.1002/adsc.202200066
|View full text |Cite
|
Sign up to set email alerts
|

DBU‐Promoted 6π‐Azaelectrocyclization and Hydrogen‐Migration to Prepare 6‐Alkyl Pyridine N‐Oxides from N‐Vinyl‐α,β‐Unsaturated Nitrones

Abstract: We describe a DBU‐controlled 6π‐azaelectrocyclization of dibenzylideneacetone‐derived N‐vinyl‐α,β‐unsaturated nitrones to prepare 6‐alkyl pyridine N‐oxides in 24–82% yields. Mechanistic studies revealed that DBU had a great impact on the formation of 6‐alkyl pyridine N‐oxides and served as a base and the carrier of hydrogen sources to in situ reduce C=C bonds. The 6‐alkyl pyridine N‐oxide was prepared at gram‐scales and converted to estrone‐derived pyridine and pyrido[2,3‐c]carbazole 4‐oxide in 46% and 52% yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…10 Focusing on the study of N -vinyl-α,β-unsaturated nitrones in our group, we reported various selective 6π-azaelectrocyclizations of N -vinyl-α,β-unsaturated nitrones to prepare isoxazolines and pyridine derivatives in the presence of iron( iii ) or nickel( ii ) catalysts and the DBU reagent (Scheme 1C). 11 Recently, we also reported a copper( i )/2-aminopyridine catalyzed 2,3-rearrangement of O -propargylic oximes to afford N -allenyl nitrone intermediates, which then underwent two types of 4π-azaelectrocyclization. 12 The aforementioned examples have shown various azaelectrocyclizations of N -vinyl nitrones.…”
mentioning
confidence: 99%
“…10 Focusing on the study of N -vinyl-α,β-unsaturated nitrones in our group, we reported various selective 6π-azaelectrocyclizations of N -vinyl-α,β-unsaturated nitrones to prepare isoxazolines and pyridine derivatives in the presence of iron( iii ) or nickel( ii ) catalysts and the DBU reagent (Scheme 1C). 11 Recently, we also reported a copper( i )/2-aminopyridine catalyzed 2,3-rearrangement of O -propargylic oximes to afford N -allenyl nitrone intermediates, which then underwent two types of 4π-azaelectrocyclization. 12 The aforementioned examples have shown various azaelectrocyclizations of N -vinyl nitrones.…”
mentioning
confidence: 99%
“…7 The hydroalkoxylation of unactivated alkenes has been achieved using Lewis acids, 8 Brønsted acids, 9 or transition metals as the catalysts (Scheme 1A). 10 For unsymmetrical alkenes, controlling the addition regioselectivity is important for the desired product formation. 11 Although these strategies have shown high efficiency and sometimes good regioselectivity, they usually suffer from harsh reaction conditions, high temperature, long reaction time, the use of explosive or toxic reagents, and expensive transition metal trace removal for purity requirements in biological and medicinal research.…”
mentioning
confidence: 99%